Analisis Dampak Program Permodalan Nasional Madani (PNM) Mekaar Dalam Perkembangan Usaha Mikro Pada Kelompok Pnm Cinta Karmel Indah - Agnesia, Chenny; Herdi, Henrikus; Rangga, Yoseph Darius Purnama (Jurnal Projemen UNIPA, 2025)
This research aimed to analyze the impact of the Permodalan Nasional Madani (PNM) Mekaar Program on the development of micro enterprises in the PNM Cintika Kamelin Indah Group in Alok Subdistrict, Sikka Regency. The research used a descriptive qualitative method with data collected through in-depth interviews, observation, and documentation. Based on Miles and Huberman’s data analysis technique, which involves data collection, data reduction, data presentation, and conclusion drawing. The results showed that the PNM Mekaar Program played an important role in supporting the growth of group members’ micro businesses through capital provision, the establishment of social networks, and the enhancement of member discipline and responsibility (through a joint liability system). Weekly meetings functioned as spaces for sharing business experiences and promoting products among members. Based on the results, the program generally had a positive impact on increasing income and the welfare of members’ families, improving business quality, and enhancing group solidarity. This research was expected to provide theoretical contributions regarding the effectiveness of microfinance programs in empowering small businesses, as well as practical input for PNM to improve its business mentoring strategies.